Reassessing Penal Dominance in Indonesian Narcotics Law Through International Legal Comparison - Gazali Ahmad; Nashriana Nashriana; Henny Yuningsih (Badan Strategi Kebijakan Hukum, 2026)
Indonesia faces significant challenges in narcotics control, particularly in balancing punitive enforcement with rehabilitation mechanisms. This study adopts a normative legal research approach to compare Law No. 35 of 2009 concerning Narcotics with the 1988 United Nations Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances. Using statutory, conceptual, and comparative approaches, this study analyzes the regulatory orientation of Indonesia’s penal and non-penal strategies, particularly as reflected in the policy framework of the National Narcotics Agency (BNN). The analysis indicates that Indonesian legislation adopts a stringent enforcement model, including the possibility of capital punishment for certain trafficking offenses, whereas international standards emphasize proportionality, international cooperation, and preventive mechanisms. Although national law formally recognizes medical and social rehabilitation, its regulatory orientation remains predominantly enforcement-centered. The study also identifies normative and institutional shortcomings in the coordination between BNN and other agencies, such as the police, the Ministry of Health, and UNODC. It highlights the need for clearer communication frameworks, strengthened rehabilitation pathways, and closer alignment between Indonesia’s narcotics legislation and international standards. By reinforcing proportional penal measures alongside structured non-penal mechanisms and enhanced inter-agency and international cooperation, Indonesia may improve the coherence of its narcotics governance framework. A balanced approach that integrates law enforcement with rehabilitation remains essential within a sustainable and legally consistent drug control strategy.